Application methods and dosages of thiamethoxam in thrips control on tomato plants - Raetano, Carlos Gilberto [UNESP]; Kobayashi, Marco Roberto [UNESP]; Kuwahara, Wagner Roberto [UNESP]; Vinchi, Rodrigo R. [UNESP] (Associação Brasileira de Horticultura, 2003)
O tripes Frankliniella schultzei Trybom (Thysanoptera: Thripidae) é um dos mais importantes vetores de tomato spotted wilt tospovirus (TSWV) na cultura do tomate no Brasil. Dois métodos de aplicação do inseticida thiamethoxam foram comparados no controle de tripes em tomate. O experimento foi conduzido em delineamento de blocos ao acaso com sete tratamentos e quatro repetições. Utilizou-se um pulverizador costal manual com lança simples provida de ponta de pulverização com jato cônico vazio JD 14-2 ou modificada, com aplicador tipo esguicho, em substituição à ponta de pulverização. Dosagens de 150 e 200 g i.a. ha-1 foram usadas em única aplicação com esguicho e 50 g i.a. ha-1 em pulverizações semanais, iniciadas aos 48 dias após a semeadura. A eficiência do inseticida em teste foi comparada com diafenthiuron (400 g i.a. ha-1), profenofos + cypermethrin (320+32 g i.a. ha-1, respectivamente) e methamidophos (60 g i.a. 100 L-1 de água), aplicados em pulverização. Não houve diferença estatística entre os métodos de aplicação e doses com thiamethoxam no controle de F. schultzei aos 24 dias após a aplicação, sendo vantajosa a realização de uma única aplicação das maiores dosagens de thiamethoxam com esguicho em comparação às aplicações semanais da menor dosagem em pulverização. A eficiência de controle do tripes com o inseticida thiamethoxam variou de 93 a 95%, nos diferentes métodos e dosagens em teste. Diafenthiuron e profenofos + cypermethrin apresentaram eficiência menor (78 e 88%, respectivamente), porém foram superiores às obtidas com methamidophos (71%). Os produtos e doses utilizados não causaram fitotoxicidade às plantas de tomate.

Thrips is one of the most important vector species of the tomato spotted wilt tospovirus (TSWV) in Brazil. Two different pesticide application methods, drench x spray, using thiamethoxam were compared with commonly used insecticides for thrips control in tomato plants, Debora Plus. The experimental design consisted of a complete randomized block design with seven treatments and four replicates. Dosages of 150 and 200 g of a.i. per ha were used in just one drench application and 50 g of a.i. ha-1 sprayed, at weekly intervals, 48 days after sowing. The control efficacy of thiamethoxam was compared to diafenthiuron (400 g of a.i. ha-1), profenofos + cypermethrin (320+32 g of a.i. ha-1, respectively) and methamidophos (60 g of a.i. per hectolitre of water) in spray application. Cumulative number of plants with tospoviruses and the F. schultzei population from ten flowers per plot were registered. The mean cumulative number of plants with tospoviruses among treatments was not significantly different. No significant difference between thiamethoxam application methods and dosages on F. schultzei control, 24 days after application, were observed for thrips population. One drench application of higher dosages of thiamethoxam proved to be more environmentally advantageous than the pesticide applied at dosages of 50 g of a.i. ha-1 at weekly intervals. The vector control efficacy of thiamethoxam varied from 93 to 95%, independently of the application method and dosages. Diafenthiuron and profenofos + cypermethrin showed less efficacy (78 and 88%, respectively) but greater than those with methamidophos (71%). The products and dosages tested did not cause phytotoxicity in tomato leaves.
Métodos de aplicação e dosagem de thiamethoxam no controle de tripes em tomate
Keywords: Lycopersicon esculentum; Frankliniella schultzei; esguicho; pulverização; controle químico; Lycopersicon esculentum; Frankliniella schultzei; drench application; spraying; chemical control